BECN2 (beclin 2) Negatively Regulates Inflammasome Sensors Through ATG9A-Dependent but ATG16L1- and LC3-Independent Non-Canonical Autophagy. Issue 2 (1st February 2022) - Deng, Guangtong; Li, Chaoran; Chen, Lang; Xing, Changsheng; Fu, Chuntang; Qian, Chen; Liu, Xin; Wang, Helen Y.; Zhu, Motao; Wang, Rong-Fu
ABSTRACT: Macroautophagy/autophagy-related proteins regulate infectious and inflammatory diseases in autophagy-dependent or -independent manner. However, the role of a newly identified mammalian-specific autophagy protein-BECN2 (beclin 2) in innate immune regulation is largely unknown. Here we showed that loss of BECN2 enhanced the activities of NLRP3, AIM2, NLRP1, and NLRC4 inflammasomes upon ligand stimulations. Mechanistically, BECN2 interacted with inflammasome sensors and mediated their degradation through a ULK1- and ATG9A-dependent, but BECN1-WIPI2-ATG16L1-LC3-independent, non-canonical autophagic pathway. BECN2 recruited inflammasome sensors on ATG9A + vesicles to form a complex (BECN2-ATG9A-sensors) upon ULK1 activation. Three soluble NSF attachment protein receptor (SNARE) proteins (SEC22A, STX5, and STX6) were further shown to mediate the BECN2-ATG9A-dependent inflammasome sensor degradation. Loss of BECN2 promoted alum-induced peritonitis, which could be rescued by the ablation of CASP1 in Becn2 -deficient mice. Hence, BECN2 negatively regulated inflammasome activation to control inflammation, serving as a potential therapeutic target for the treatment of infectious and inflammatory diseases. Abbreviations : AIM2: absent in melanoma 2; ATG: autophagy related; BECN1: beclin 1; BMDC: bone marrow-derived dendritic cells; BMDM: bone marrow-derived macrophages; CASP1: caspase 1; CQ: chloroquine; gMDSC: granulocytic myeloid-derived suppressor cells; IL: interleukin; LPS: lipopolysaccharide; MAP1LC3B: microtubule associated protein 1 light chain 3 beta; mMDSC: monocytic myeloid-derived suppressor cells; NLRC4: NLR family CARD domain containing 4; NLRP1: NLR family pyrin domain containing 1; NLRP3: NLR family pyrin domain containing 3; PECs: peritoneal exudate cells; PYCARD/ASC: apoptosis-associated speck-like protein containing a caspase activation and recruitment domain; SNAREs: soluble NSF attachment protein receptors; STX5: syntaxin 5; STX6: syntaxin 6; ULK1: unc-51 like autophagy activating kinase 1; WIPI: WD repeat domain, phosphoinositide interacting.